2014
DOI: 10.1038/hdy.2014.10
|View full text |Cite
|
Sign up to set email alerts
|

Post-natal imprinting: evidence from marsupials

Abstract: Genomic imprinting has been identified in therian (eutherian and marsupial) mammals but not in prototherian (monotreme) mammals. Imprinting has an important role in optimising pre-natal nutrition and growth, and most imprinted genes are expressed and imprinted in the placenta and developing fetus. In marsupials, however, the placental attachment is short-lived, and most growth and development occurs post-natally, supported by a changing milk composition tailor-made for each stage of development. Therefore ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 125 publications
(179 reference statements)
3
22
0
Order By: Relevance
“…We support the idea first proposed for marsupial mammals (Stringer et al, ), that the mammary gland represents the functional equivalent of the placenta in the postnatal stage of eutherian mammals. Both these organs support the normal growth and development of the offspring.…”
Section: Functional Comparison Between the Placenta And The Mammary Gsupporting
confidence: 91%
See 2 more Smart Citations
“…We support the idea first proposed for marsupial mammals (Stringer et al, ), that the mammary gland represents the functional equivalent of the placenta in the postnatal stage of eutherian mammals. Both these organs support the normal growth and development of the offspring.…”
Section: Functional Comparison Between the Placenta And The Mammary Gsupporting
confidence: 91%
“…In marsupials, a smaller subset of genes is imprinted compared to eutherian mammals, pregnancy is shorter, and the major provision of nutrition is supplied through suckling, with the mammary gland delivering milk to the altricial neonate. Renfree and coauthors identified the specific imprinting of insulin ( Ins2 in mice) and IGF2 in this tissue (Stringer et al, ), and proposed that the marsupial mammary gland would therefore be a preferred site of imprinting because of its predominant role in nutritional support of its altricial neonate (Stringer et al, ). They have proposed that imprinting in the marsupial mammary gland parallels eutherian placenta imprinting.…”
Section: Evidence For Imprinting In the Mammary Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the Kinship and Maternal‐Offspring Coadaptation Theories were challenged by the discovery that many genes show imprinted expression after individuals are no longer receiving parental care (Wilkinson et al ), including many expressed in the brain that affect social behavior (Davies et al ; Wilkinson et al ; Garfield et al ), and several expressed in the mammary gland (Stringer et al , ; Cowley et al ). The Kinship Theory has been generalized to include all interactions between relatives, with selection for imprinting resulting from relatedness asymmetries (such as those arising from sex‐biased dispersal or reproductive success) that generate conflict over the expression level favored by the matrigenic and patrigenic gene copies (Úbeda and Gardner , ).…”
Section: Introductionmentioning
confidence: 99%
“…The paper by Stringer et al (2014) notes that imprinting has a critical role in eutherian pregnancy, with most imprinted genes expressed in the placenta and fetus. In marsupials, however, pregnancy is much shorter and the part of the eutherian placenta in supplying nutrition to the developing fetus is instead played by the mammary gland delivering milk to the altricial neonate.…”
mentioning
confidence: 99%